Solidarity Tax as a Part of the Personal Income Tax in Poland After 2019 In Comparison with Selected European Countries - Pach JANINA (Communications of International Proceedings, 2025)
Income tax in Poland has been subject to many changes, covering the structural elements of this tax, including tax rates, tax reliefs and exemptions. In 2019 solidarity levy was introduced into income tax solutions, called the "third threshold" in personal income tax. The main aim of the article is to present the essence of personal income tax in Poland, the directions of changes, with particular emphasis on the solidarity levy. What are the structure and main goals of this tribute and what are the arguments for maintaining it - this is the main research problem. The results of research and analyzes regarding this levy, which supplies the Solidarity Fund, will be used to verify the research hypothesis that: the solidarity levy introduced in Poland after 2019 plays an increasingly important role in financing disabled people, however, it requires many changes. The paper also includes the comparison of solidarity levy in selected European countries.
Keywords: personal income tax; tax thresholds; solidarity levy; Solidarity Fund.